T cell reactivity of defined peptides from a major Plasmodium falciparum vaccine candidate: the Pf155/RESA antigen. - Troye-Blomberg, M; Kabilan, L; Riley, E; Ortlund, J; Andersson, G; Perlmann, H; Olerup, O; Högh, B; Petersen, E; Snow, R (1988)
Several immunodominant B-cell epitopes of the P. falciparum antigen blood stage Pf155/RESA, a major vaccine candidate antigen, are located in the molecular regions containing amino acid repeats. We started to map Pf155/RESA for T cell reactive epitopes. For this purpose, short synthetic peptides corresponding to the 3'- and 5' repeat regions of the molecule as well as to non-repeated sequences outside these regions were prepared. T cells from P. falciparum primed donors from two highly endemic areas of Africa were tested for their responsiveness to the peptides by thymidine incorporation and/or interferon gamma (IFN-gamma) release. There was a considerable variation in the response to the different peptides. However, the strongest and most frequent responses were seen with a few peptides from the 3'- and 5'-repeat regions. Thus, the immunodominant B cell epitope regions of Pf155/RESA, contain several T cell epitopes. Since the repeat regions are known to be conserved in different P. falciparum strains, the T cell epitopes reported here may be suitable constituents of a P. falciparum subunit vaccine.